2020
DOI: 10.1016/j.jcol.2020.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of COVID-19 on colorectal disease management

Abstract: The current recommendations for management of colorectal diseases are still evolving, due to the limited experience on this issue. As the new coronavirus can be transmitted through breath droplets, by contact and orofecally, there is no consensus of how this fact may affect the investigation and treatment of anorectal diseases. Thus, high-quality multicenter studies are urgently needed to provide better information to both patients and the multiprofessional team, in order to build an effective pandemic respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Temporizing treatment strategies, such as short-course radiotherapy with prolonged wait to surgery, were used to minimize the effect of delaying CRC resection. 17 Patients with locally advanced rectal cancer who might previously have been considered for pelvic exenteration were deferred because of the resource intensity of this procedure and the expectation that outcomes would be negatively affected in the event of acquiring nosocomial COVID-19 infection during a more prolonged hospital stay. Similarly, patients with metastatic disease may have been offered stenting and systemic anticancer therapy or best supportive care rather than palliative resection of a symptomatic primary tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temporizing treatment strategies, such as short-course radiotherapy with prolonged wait to surgery, were used to minimize the effect of delaying CRC resection. 17 Patients with locally advanced rectal cancer who might previously have been considered for pelvic exenteration were deferred because of the resource intensity of this procedure and the expectation that outcomes would be negatively affected in the event of acquiring nosocomial COVID-19 infection during a more prolonged hospital stay. Similarly, patients with metastatic disease may have been offered stenting and systemic anticancer therapy or best supportive care rather than palliative resection of a symptomatic primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In the English National Health Service (NHS), one approach to reduce the risk of patients acquiring COVID-19 while in hospital has been the separation of hospitals into “cold” sites used for patients free of COVID-19 and “hot” sites used for all other patients. 17 , 18 Preoperative isolation and COVID-19 swab testing were used in patients having surgery in “cold” and “hot” sites to reduce the risk of community acquired infection. The effectiveness of separating CRC services in this way is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…The association of COVID-19 infection with elevation resulted in unreliability of the biomarker for surveillance of CRC during the COVID-19 pandemic. Social distancing and lockdown measures made access to colonoscopy difficult during the pandemic, and the use of open access colonoscopy and capsule colonoscopy in surveillance of CRC was encouraged[ 25 , 27 , 33 , 50 , 55 ].…”
Section: Screening and Surveillance For Colorectal Cancermentioning
confidence: 99%
“…They also noticed an increase of patients with stage III and stage IV from 22.2% and 19.0% to 26.8% and 26.2%, respectively[ 16 , 62 ]. These changes were attributed to the delays in screening and diagnosis of CRC that was caused by the COVID-19 pandemic[ 17 , 55 , 62 ]. The mode of presentation was also affected by the pandemic as Shinkwin et al [ 59 ] reported an increase in emergency presentation from 28.6% to 36.0%.…”
Section: Clinical Presentation Of Colorectal Cancermentioning
confidence: 99%
“…Multiprofessional team should have a prior set up plan in order to act urgently with a clear set up strategic therapeutic plan to avoid long term complications of postpending management due to restrictions set due to COVID. 1 Colorectal cancer globally is the second leading cause of cancer deaths, and due to the pandemic adverse outcomes including delay in colorectal follow up clinics, this greatly affected the survival outcomes.…”
Section: Impact Of Covid Pandemic On Colorectal Cancermentioning
confidence: 99%